+0  
 
0
56
1
avatar

Solve (2x + 4)/(x^2 + 4x - 5) = (2 - x)/(x + 5).

 Feb 20, 2021

Best Answer 

 #1
avatar+944 
+1

\(\frac{2x+4}{x^2+4x-5} = \frac{2-x}{x+5}\)

 

\((2x+4)(x+5) = (2-x)(x^2+4x-5)\)

 

\(2(x+2)(x+5) = -(x-2)(x+5)(x-1)\)

 

\(2(x+2) = -(x^2-3x+2)\)

 

\(2x+4 = -x^3+3x-2\)

 

\(x^2 - x + 6 = 0\)

 

\(\boxed{x = -3, 2}\)

.
 Feb 20, 2021
 #1
avatar+944 
+1
Best Answer

\(\frac{2x+4}{x^2+4x-5} = \frac{2-x}{x+5}\)

 

\((2x+4)(x+5) = (2-x)(x^2+4x-5)\)

 

\(2(x+2)(x+5) = -(x-2)(x+5)(x-1)\)

 

\(2(x+2) = -(x^2-3x+2)\)

 

\(2x+4 = -x^3+3x-2\)

 

\(x^2 - x + 6 = 0\)

 

\(\boxed{x = -3, 2}\)

CubeyThePenguin Feb 20, 2021

20 Online Users

avatar